Shaping a Communitarian Ethos in an Era of Ecological Crisis - Barkin, David (Frontiers in Sustainability, 2022)
In response to the deep social and ecological crisis for which the international community is proving incapable of attenuating, many Peasants and Indigenous peoples in Mexico, and in other parts of the Global South, are transforming their visions of their futures, shaping a new ethos of self-management and conviviality, consistent with a responsible relationship to their territories. From the vantage point of the Global South, these peoples constitute a social and economic force that is altering the social and productive dynamics in many countries, proposing models of organization and building alliances among themselves regionally and internationally to exchange information, develop common strategies, and provide political support. In Mexico, many continue to produce traditional crops, while modifying their techniques to incorporate agroecological experiences from other communities, diversifying output and protecting the environment. Recently, they are enriching local practices with a systematisation of their inherited traditions and cosmologies, creating effective models of social, political and environmental organisation that lend authority to their claims to be able to manage their territories autonomously. There is a growing body of scientific literature that substantiates this capacity, demonstrating that the collective knowledge of the global networks of local communities is more effective in protecting biodiversity and attending to their own basic needs while improving their quality of life than that of societies more fully integrated into the global economy. In conclusion, we describe how these visions are shaping international networks, defining new channels for collaboration, improving the quality of life for people in these communities, while protecting them from the continuing incursions of capital.